تطوير الأدارة الألكترونية وتحدياتها في مصلحة الأحوال المدنية ليبيا - Bashir Masoud Abdullah Aoun (Universiti Sains Islam Malaysia, 2024)
Rapid developments in science and technology, using information and communications technology (ICT) applications in management and scientific researches, have made electronic management (E-Management) a vital element in the organisation. This research is based on the Islamic Fiqh which organises the relationship between human beings and the Creator, among individuals and groups and among Muslim countries and non-Muslim countries. It is relevant to all government organisations in Libya, which is in the process of developing E-Management in its administration. The system uses technology to improve and facilitate the governing process besides maintaining electronic records for the best performance and results of the work flow integration of information. E-Management, which is in line with Libya's efforts to modernise the government administration, would be considered an important database for citizens as well as all government organisations in that country. The main aim of this research is to contribute to the process of developing electronic management and to identify the challenges in the Libyan government's administrative management and the Civil Status Authority. It uses the descriptive approach and the questionnaire as a tool to get information. The study shows that 61.8 per cent of the respondents interviewed are of the opinion that using modern technology in the Civil Status Authority in Libya affect and contribute to the development of E-Management. Of those interviewed, 58.8 per cent are of the view that having qualified human resources in the Civil Status Authority in Libya contributes to the development of E-Management.